2016
DOI: 10.1158/0008-5472.can-15-0869
|View full text |Cite
|
Sign up to set email alerts
|

M-CSF and GM-CSF Receptor Signaling Differentially Regulate Monocyte Maturation and Macrophage Polarization in the Tumor Microenvironment

Abstract: Tumors contain a heterogeneous myeloid fraction comprised of discrete MHC-II hi and MHC-II lo tumor-associated macrophage (TAM) subpopulations that originate from Ly6C hi monocytes. However, the mechanisms regulating the abundance and phenotype of distinct TAM subsets remain unknown. Here, we investigated the role of macrophage colony-stimulating factor (M-CSF) in TAM differentiation and polarization in different mouse tumor models. We demonstrate that treatment of tumor-bearing mice with a blocking anti-M-CSF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
188
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(199 citation statements)
references
References 19 publications
(30 reference statements)
10
188
0
1
Order By: Relevance
“…CS7-treated MAMs displayed activated signaling pathways of TREM-1, GM-CSF, LPS-stimulated MAPK, and production of nitric oxide and iNOS (Figure 2b) that are highly related to M1 MΦ polarization and function. 24, 3335 CS7-treated MAMs also displayed activated pathways of interferon, macropinocytosis, JAK1, JAK2, and TYK2 (Figure 2b), which are also M1 MΦ-specific gene clusters 36 . Quantitative RT-PCR showed that 5TGM1-cocultured MΦs (MAMs) expressed greater mRNA levels of M2 MΦ-associated Irf4, Arg1 , and Il10 and lower levels of M1 MΦ-associated Il12a and Tnfα than untreated MΦs, whereas Irf4 and Il10 mRNA levels were decreased and Tnfa and Nos2 levels were elevated in CS7-treated MAMs (Figure 2c).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…CS7-treated MAMs displayed activated signaling pathways of TREM-1, GM-CSF, LPS-stimulated MAPK, and production of nitric oxide and iNOS (Figure 2b) that are highly related to M1 MΦ polarization and function. 24, 3335 CS7-treated MAMs also displayed activated pathways of interferon, macropinocytosis, JAK1, JAK2, and TYK2 (Figure 2b), which are also M1 MΦ-specific gene clusters 36 . Quantitative RT-PCR showed that 5TGM1-cocultured MΦs (MAMs) expressed greater mRNA levels of M2 MΦ-associated Irf4, Arg1 , and Il10 and lower levels of M1 MΦ-associated Il12a and Tnfα than untreated MΦs, whereas Irf4 and Il10 mRNA levels were decreased and Tnfa and Nos2 levels were elevated in CS7-treated MAMs (Figure 2c).…”
Section: Resultsmentioning
confidence: 94%
“…We also determined the effect of CS7 on in vitro polarized M1 or M2 MΦs. CS7 treatment significantly and specifically reduced the viability (Figure 1b) and increased apoptosis (Supplementary Figure 1g) of IL-10- or IL-4-polarized M2 MΦs 2123 and MAMs, but had minimal effect on GM-CSF- or LPS plus IFN-γ-polarized M1 MΦs 24, 25 . Interestingly, CS7 treatment significantly downregulated the expression of pAkt and pERK in M2 MΦs and MAMs but not in M1 MΦs (Figure 1c).…”
Section: Resultsmentioning
confidence: 97%
“…transplantation) macrophage polarization.. In this respect, the development of monoclonal antibodies that target macrophage polarization through CSF1 receptor signaling has been shown to interfere with macrophage differentiation/proliferation and to prevent tumor progression (33, 34). …”
Section: Discussionmentioning
confidence: 99%
“…26 In addition, M-CSF, a secreted cytokine derived from various cells, is known to be a crucial regulator for the differentiation, recruitment, and polarization of macrophages. 17,18 Therefore, we were intrigued to speculate that hypoxia-induced ATF4 may promote progression of proliferating IH through recruitment of macrophages into tumor tissues via induction of M-CSF. To test this hypothesis, we first evaluated the expression of M-CSF and its association with ATF4 at different stages of IHs.…”
Section: Discussionmentioning
confidence: 99%
“…15 Macrophage colony-stimulating factor (M-CSF) is a wellknown key regulator for the differentiation, polarization, and survival of macrophages among a broad spectrum of pathologies. [16][17][18] However, whether hypoxia, a wellestablished driving force in IH progression, may affect or regulate macrophages in IH remains largely unknown. Besides, how the infiltration of M2-polarized macrophages in proliferating IH is modulated is still far from clear.…”
mentioning
confidence: 99%